(x+6)(x+6)=49

Simple and best practice solution for (x+6)(x+6)=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+6)(x+6)=49 equation:


Simplifying
(x + 6)(x + 6) = 49

Reorder the terms:
(6 + x)(x + 6) = 49

Reorder the terms:
(6 + x)(6 + x) = 49

Multiply (6 + x) * (6 + x)
(6(6 + x) + x(6 + x)) = 49
((6 * 6 + x * 6) + x(6 + x)) = 49
((36 + 6x) + x(6 + x)) = 49
(36 + 6x + (6 * x + x * x)) = 49
(36 + 6x + (6x + x2)) = 49

Combine like terms: 6x + 6x = 12x
(36 + 12x + x2) = 49

Solving
36 + 12x + x2 = 49

Solving for variable 'x'.

Reorder the terms:
36 + -49 + 12x + x2 = 49 + -49

Combine like terms: 36 + -49 = -13
-13 + 12x + x2 = 49 + -49

Combine like terms: 49 + -49 = 0
-13 + 12x + x2 = 0

Factor a trinomial.
(-13 + -1x)(1 + -1x) = 0

Subproblem 1

Set the factor '(-13 + -1x)' equal to zero and attempt to solve: Simplifying -13 + -1x = 0 Solving -13 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = 0 + 13 -1x = 0 + 13 Combine like terms: 0 + 13 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {-13, 1}

See similar equations:

| (y-8)(y-8)-28=0 | | 3y+x=-9 | | 3m+1=3m^2+6m+2 | | x+17+12=35 | | 2v^2-13v+47=(v-7)(v-7) | | X+(x+6)=33 | | 10x=-52 | | (y-1)(y-1)=2y^2+6y+16 | | ((2/3)a)+2=((1/3)(4a+1)) | | 2w^2-14w+33=(w-6)(w-6) | | y^2+17y=72-0 | | 3(x-2)/2=-3x | | 10x=52 | | I=300*.11*2 | | 70x+10y=100 | | 3/4x+y=4 | | x^2-13x+6.5=0 | | -20x=4x^2+25 | | 2t^2+7t-4=0 | | (2/3)a+2=(1/3)(4a+1) | | -x-(2/5)=x+(1/2)+(1/5) | | y=-10+10 | | 75-(-10)= | | 5p-3=12p+11 | | 1/3d=60 | | 5u^2+20u=0 | | 12+.45x=20 | | 6w^2-12w=0 | | 8.4+6.7*8/8 | | 6h=358 | | 4y^2=-20y | | 3ln(7x)=12 |

Equations solver categories